NO ALINHAVO DO TEMPO: o tecer da memória no romance Por Onde Deus Não Andou, de Godofredo Viana - NORATO, Kerllen Miryan Portela de Paiva (2017)
The present research consists in to analyze how the memory permeates the novel Por Onde Deus Não Andou, by the writer from Maranhão, Godofredo Viana, from the comprehension of the memory concept and its ramifications as one of the threads of literary creation. On this sense, it will be pointed the relations between memory and literature, as well their points of contact with landscape. Furthermore, it will be approached questions about the 30’s novel, to locate the author and the work, that, for questions of anachronism doesn’t appear on regionalist canon, but, it has the characteristics of a regional novel and then to analyze the elements that compound the universe of memory presents on the work, to know: the babaçu coconut, the legends and folklore, the customs and traditions and the landscape.